Addressing the challenges of COVID‐19 pandemic outbreak: Pakistan's preparations and response. Issue 4 (16th September 2020) - Meo, Muhammad S.; Sabir, Samina; Chaudhry, Imran S.; Batool, Saima; Farooq, Fatima
Abstract : This study examines the challenges faced by Pakistan during COVID‐19 pandemic and the policies taken by the Government of Pakistan to contain and control the spread of the pandemic. Pakistan is considered among those countries that have been severely affected by COVID‐19 due to insufficient health infrastructure. Moreover, the pandemic has affected the country socially and economically, which has slashed down GDP and overall wellbeing. However, the government has taken effective policy measures that enhanced the recovery rate of infected patients, for instance, out of 276, 288 confirmed cases, 244, 883 cases have been recovered. Currently, only 26, 421 cases are active; it shows 88.6% recovery. Since the implementation of consistent plans, policies, and effective actions, the recovery rate has been ramping up, and infected cases have been getting down.